HUBUNGAN STIMULASI OLEH ORANG TUA TERHADAP PERKEMBANGAN MOTORIK HALUS PADA ANAK USIA PRASEKOLAH (3 - 5 TAHUN) - Yektiningsih, Erwin; Erviana, Munika (Jurnal AKP, 2014)
Development fine motor adaptive is something which have correlation with ability of preschool child to observe something and do some movement which is involve of certain body parts and small muscles, need some accurate coordination, also doesnât need to much power. The purpose of this research is to know the correlation of parentâs stimulation to development fine motor adaptive for preschool 3-5 years.Design of this research is using analytic cross sectional with purposive sampling technic. The process of taking data were used quesioner and some observation, than in this research could get 27 respondents and 15 sample of respondents. Data which have tabulation presented in form of pie diagram and column.The results of research showed that the parentâs give stimulation for always 3 respondents (20%), for often 4 respondents (26,7%), for sometimes 4 respondents (26,7%), for never 4 respondents (26,7%). And development fine motor adaptive for child normal 4 respondents (27%), for unsertain 8 respondents (53%), for deviationÂ  3 respondents (20%). While the parentâs that always give stimulation for child could produce development fine motor adaptive normal for 2 respondents (13,3%) and parentâs who never give stimulation for child could produce development fine motor adaptive in uncertain for 3 respondents (20%). The research result was done by data counting used spearman rho with signified value (p=0,688) < (a=0,01) that meaned H1 is accept and Ho is unaccept.Â Â Â  According from above research we can concluded that there is a correlation of parentâs stimulation to development fine motor adaptive for preschool 3-5 year.Â Keyword : Stimulation, Parentâs, Development, Fine Motor Adaptive, Preschool 3-5 Years.